PEMAKNAAN IKLAN NEW ERA BOOTS (Makna Penari Wanita Dan Binaraga Dalam Iklan New Era Boots) - Susanto, Danang Ari (Transformasi, 2016)
This study departs from advertising new era boots which is one of the ads are blocked by KPIS.The commercials broadcast during the period February 2015 has violated the regulation ofbroadcasting set KPI. The infringing content is pornographic content that are clearlydesignated as Indonesia in broadcasting content are prohibited for publication. The content ofthe elements of pornography can be seen from some of the scenes contained objects with tightclothes and sexy and there is a scene of men – men are shirtless. The purpose of this study wasto describe the meaning of the message contained in the new era of advertising bootsDengananalysis of semiotics Roland Barthes, the results obtained in this research is the reality of theobject in the ad showed about the quality of the product in the form of elasticity, comfort, andstrength. It refers to an object which is used, namely a flexible women dancers in dancing aswell as a large and muscular bodybuilding-body stout.Keywords: advertising new era boots, semiotics, the meaning of a message